2017
DOI: 10.1007/s11325-017-1503-8
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea increases the risk of cardiac events after percutaneous coronary intervention: a meta-analysis of prospective cohort studies

Abstract: In patients after PCI, OSA appears to increase the risk of cardiac death, non-fatal MI, and coronary revascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 32 publications
2
19
0
1
Order By: Relevance
“…Systematic reviews: Nine studies were included [44][45][46][47][48][49][50][51][52]. The original studies included in the systemic reviews were of class I and II quality.…”
Section: Results Of Literature Searchmentioning
confidence: 99%
“…Systematic reviews: Nine studies were included [44][45][46][47][48][49][50][51][52]. The original studies included in the systemic reviews were of class I and II quality.…”
Section: Results Of Literature Searchmentioning
confidence: 99%
“…Up to 66% of ACS patients have OSA and about 50% of patients with PCI suffer from OSA 3, 4, 5. Meta‐analysis demonstrated that cardiac death is 2‐fold higher in patients with OSA after successful PCI 4. The OSA patients also have more aggressive atherosclerotic disease and a greater risk of thrombotic complications, including stent thrombosis 22.…”
Section: Discussionmentioning
confidence: 99%
“…A prevalence of OSA up to 66% has been reported in the early phase of acute coronary syndrome (ACS) 3. And about 50% of patients with percutaneous coronary intervention (PCI) suffer from OSA 4, 5. Importantly, patients with OSA experience an increased risk of adverse outcomes after PCI 4, 5.…”
mentioning
confidence: 99%
See 2 more Smart Citations